Parks/sports facilities in local communities and the onset of functional disability among older adults in Japan: The J-shaped spatial spillover effects. (May 2022) - Takagi, Daisuke; Kondo, Naoki; Tsuji, Taishi; Kondo, Katsunori
Abstract: We examined the associations between parks/sports facilities in local communities and the onset of functional disability among Japanese older adults. We further investigated the spatial spillover effects of parks/sports facilities in 1st-, 2nd-, and 3rd-degree neighboring communities. Data on the onset of functional disability, including date of onset, sex, age, and address (school district) of all older adults aged 65 years and older living in Kobe City were obtained from the public long-term care insurance database (163, 348 men [190, 831 person-year] and 200, 443 women [230, 464 person-year]). Multilevel proportional hazard regression analyses showed that the number of parks and sports facilities were negatively associated with the onset of functional disability among men. In particular, these associations were stronger for the adjacent district than for individuals' living districts. Our results imply that involving multiple neighboring communities as the intervention unit is effective when utilizing community built environments for long-term care prevention in men. Highlights: Parks/sports facilities are associated with functional disability among older men. Especially, those in adjacent districts show stronger associations. The associations are not marked among older women. Utilizing multiple districts may be effective for preventive intervention for men.